Confucius, a Yugoslav Nationalist: Representations of Confucianism in pre-WWII Slovenia - Motoh, Helena (Poligrafi, 2019)
The aim of the present paper is to analyse the representations of Confucianism in early 20th century Slovenia and reflect on the role of external factors – historical and political events of the time, Yugoslav internal and external political developments, social and economic changes, etc. – in these interpretations of Confucian tradition. In the virtual absence of books on the topic, the main source for assessing what the representations of Confucianism were like in the period will be journal and newspaper articles (more than 500 texts in a vast array of genres). The material analysed is limited by the time of publication to encompass the last two decades of the 19th and the first four decades of the 20th century, and only publications published in Slovenian and on the territory of today’s Slovenia are used. The topic of the paper, early 20th century representations of Chinese thought, has not been explored extensively in scholarly works. By an analysis of the 1884–1941 representations of Confucianism and Confucius in Slovenian press, the present paper aims to partly fill this gap, while also exploring the outside factors which had an impact on the type of discourse produced about Confucius and Confucianism in the period.